(3bWa GdCRgGQ ef GdNWW hGdCKGQs - (3CHh YHO Gddg eMeO Hf CHi GdSQhQ GdUOjbi GdHcQis; (3Jbj GdOjf CMeO Hf Ydj Hf YHO GdbGOQ GdebQjRj GdeUQj,J (B854 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CWdY TeS GdSQhQ HgPg GdOjGQ GdeUQjI hHYO , Efi deG WGdYJ cJGH GdNWW hGdBKGQ aQCjI CSgH ajg ZGjI GdESgGH s
(3BNQgG (B:s
(3hHfGMjI SHc cfjSI eMOKI hHGdJMQjQjI cfjJg eMOKg ai HjJ eNai Je GdcJGH GdeNJUQ GdeSei HbWa GdCRgGQ ef GdNWW hGdBKGQ s
(3HgG fXGe GdJYbjHIs
(3hQO GdYfhGf GdCUdi ai c X (B1 / 715s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(266(3b(B) s
Keywords: (3GdLZQGajG h GdHdOGfs